Judicial control of administration in Kosovo - Bashkim Rrahmani (Juridical Tribune, 2018)
The development of administration went through various phases after the war in Kosovo (1999). Right after the war we cannot talk about the clear administration with the local sense, since Kosovo based on the UN Security Council Resolution 1244 was put under the international civil administration. Ten years later Kosovo Parliament approved the Declaration of Independence after which the Kosovo Constitution was adopted, whose main attribute was to create the state of Kosovo. Thus, based on this, the administration in Kosovo was developed firstly as the internationally organized one; then it was locally organized supervised by the international power and finally it is being developed based on Kosovo Constitution and Kosovo Laws. With this paper author by explaining the process of administration development, using: method of historical analysis, method of comparison analysis, method of systemic analysis, etc., with the specific analysis of the judicial control of Kosovo administration during these phases, as the basic form of the administration control which is exercised by courts in Kosovo. Conclusions and recommendations of the paper are expected to be used not only for academic debates.